Impact of trends in new and emerging contact allergens - Olaf Rodriguez, MD; Bruce A. Brod, MD, MHCI; William D. James, MD (Wolters Kluwer, 2022)
Allergic contact dermatitis represents a T cell-mediated, delayed-type hypersensitivity response to exogenous agents. While allergic contact dermatitis is one of the most common causes of skin disease encountered by dermatologists, emerging trends within the field are in constant flux, as influenced by ever-changing industry practices and evolving consumer behaviors. Although certain allergens continue to predominate, new chemicals are frequently being introduced, thus shifting the pattern of allergen exposure and sensitization. This review examines the impact of trends in new and emerging contact allergens, with particular attention to clinical contexts in which these agents may be encountered. In addition, we offer a working knowledge of these allergens' characteristics, sources, and relevance, while outlining recommendations to accurately evaluate, diagnose, and provide appropriate counseling for these diseases.